The Influence Of Service Quality And Convenience On Trust In Order To Increase Customer Satisfaction At The Bungo Tanjung Restaurant - Miftah Faridh; Puji Odarwani; Rusdiyanto Rusdiyanto; Metri Hidayati (Utan Kayu Publishing, 2025)
Research on Rumah Makan Bungo Tanjung with the formulation of the problem: How does service quality and comfort affect trust in order to increase consumer satisfaction in Rumah Makan Bungo Tanjung? The population used in this study were all consumers at Rumah Makan Bungo Tanjung totaling 100 respondents. The sampling technique used accidental sampling based on predetermined criteria totaling 100 respondents. Using SPSS 26. Based on the results of research that has been done about the effect of Service Quality, Convenience, on Trust in order to increase Consumer Satisfaction in using Rumah Makan Bungo Tanjung Services it can be concluded as follows: Service Quality affects trust in using services. Convenience affects trust in using services. Trust affects consumer satisfaction in using services. Service Quality has an indirect effect on consumer satisfaction in using services. Convenience has an indirect effect on consumer satisfaction in using services. Trust in Customer Satisfaction of Rumah Makan Bungo Tanjung has positive and significant influence between Service Quality on Consumer.